Determination of vitamin E and its metabolites in equine urine using liquid chromatography–mass spectrometry. Issue 6 (9th February 2021) - Favro, Gianna; Habib, Hadi; Gennity, Ingrid; Puschner, Birgit; Hales, Erin N.; Finno, Carrie J.; Moeller, Benjamin C.
Abstract: Equine neuroaxonal dystrophy/degenerative myeloencephalopathy (eNAD/EDM) is a hereditary, deteriorating central nervous disease in horses. Currently, the only way to confirm eNAD/EDM is through a postmortem histological evaluation of the central nervous system. Vitamin E, specifically the isoform alpha‐tocopherol (α‐TP), is known to protect eNAD/EDM susceptible horses from developing the clinical phenotype. While vitamin E is an essential nutrient in the diet of horses, there are no diagnostic tests able to quantitate vitamin E and its metabolites in urine. An ultra‐performance liquid chromatography‐atmospheric‐pressure chemical ionization mass spectrometry (UPLC‐APCI‐MS/MS) method was developed and validated following acidic hydrolysis and solid phase extraction to quantitate vitamin E and its metabolites in equine urine. A blank control horse urine matrix was used and spiked with different concentrations of analytes to form a standard curve using either alpha‐tocopherol‐d6 or chlorpropamide as the internal standard. Inter‐day and intra‐day statistics were performed to evaluate the method for accuracy (90% to 116%) and precision (0.75% to 14%). Matrix effects, percent recovery, and stability were also assessed. The method successfully analyzed alpha‐carboxyethyl hydroxychroman (α‐CEHC), alpha‐carboxymethylbutyl hydroxychromans (α‐CMBHC), gamma‐carboxyethyl hydroxychroman γ‐CEHC, and α‐TP concentrations in urine to determine a baseline levels of analytes in healthy horses, and can be used to determine concentrations of vitamin E metabolites in equine urine allowing for its evaluation as a diagnostic approach in the treatment of eNAD/EDM. Abstract : Development and validation of an LC‐MS/MS method for the determination of Vitamin E and its metabolites in equine urine.